Aerosol penetration through fabrics: Experiments and theory. Issue 3 (11th November 2020) - He, Meilu; Ghee, Terence A.; Dhaniyala, Suresh
Abstract: Clothing or garments have been widely used to prevent dermal contact from particles. During the current COVID-19 pandemic, there has been a renewed focus on the role of clothing for personal protection. Insufficient attention has, however, been given to understand the relation between fabric parameters and fabric performance for filtration. In this study, two different fabric materials (10 oz denim and A30) were experimentally tested. The performance of the materials was estimated through both a benchtop test, similar to that used in filter performance studies, and a sleeve test which simulates a segment of the human body. The benchtop test established the relation among face velocity, pressure drop, and penetration. In the sleeve test, aerosol penetrations were determined for different sampling angles and wind conditions. In addition to individual fabric test, penetration measurements were also made with the combination of the two fabrics. The experimental results were used to test the performance of the fabric penetration model that was developed as part of this study. Our fabric penetration model is based on inhomogeneous filtration theory with fiber parameters optimized by experimental benchtop penetration results. The fabric penetration model was used to predict the performance of a fabric sleeve system. The theoretical predictions match with the experimental results well for free stream velocities in the range of 9 to 18 m s −1 . Therefore, without expensive experimental test operation under elevated wind conditions, the penetration of a fabric at different operation conditions can be predicted based on the experimental results in benchtop test. Copyright © 2020 American Association for Aerosol Research